Feasibility of repeated session error-augmentation gait training for people with nontraumatic transtibial amputation. Issue 6 (25th December 2022) - Kline, Paul W.; Davis-Wilson, Hope C.; So, Noel F.; Fields, Thomas T.; Christiansen, Cory L.
Abstract : Background: Spatiotemporal gait asymmetries are a persistent problem for people with non-traumatic lower-limb amputation. To date, there is limited knowledge of multi-session gait training interventions targeting step length symmetry after non-traumatic amputation. Objective: The objective was to evaluate the feasibility and efficacy of an eight-session, treadmill-based error-augmentation gait training (EAT) protocol to improve spatiotemporal gait asymmetry in people with non-traumatic transtibial amputation (TTA). Study Design: Pre-post, single group. Methods: The EAT protocol involved eight training sessions (twice per week, four weeks) of supervised split-belt treadmill walking with asymmetrical belt speeds for five, three-minute sets each session. Step length symmetry during overground walking at a self-selected gait speed was assessed prior to, weekly, and one-week after the EAT protocol. Feasibility outcomes included protocol fidelity, safety, participant acceptability, and efficacy. Results: Seven of the eight participants (87.5%) completed the intervention at the prescribed dose. One participant developed a skin blister on their residual limb, which was possibly related to the intervention. No falls, musculoskeletal injuries, or increases in pain occurred. Participants rated EAT as acceptable based on scores on the Intrinsic Motivation Inventory – Interest/Enjoyment subscale (6.6 ± 0.5; mean ± SD). Average between-limb step length Normalized Symmetry Index improved (was reduced) one-week following EAT (2.41 ± 6.6) compared to baseline (5.47 ± 4.91) indicating a moderate effect size (d=0.53). Conclusions: An eight session EAT program delivered over four weeks using a split-belt treadmill is feasible for people with unilateral non-traumatic TTA and may reduce step length asymmetry up to a week after intervention.